KONSTRUKSI KONSEP SOCIAL DISTANCING DAN LOCKDOWN DALAM PERSPEKTIF KEBIJAKAN PUBLIK - Dian Herdiana (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
The outbreak of COVID-19 that hit the world gave rise to new terminology in the community, namely lockdown and social distancing. Both of these terms refer to the efforts made by the government in tackling COVID-19. Social distancing is a government policy that is built based on a reductive effort towards the spread of disease in an area which has implications for the limitation of activities of the population with the consequence of the government's obligation to set policy instruments for determining the spatial pattern of activity of each population. Lockdown is a government policy that is built on the condition of spreading of the disease that has spread widely in an area which has implications for systematic population restrictions in the region with the consequence of the government's obligation to set policy instruments for the survival of the population. Based on this understanding, the government's position in the context of social distancing policy acts as a regulator and determinant of the activities of the population which within certain limits the population still has access to livelihoods, while the government's position in the context of the lockdown policy acts as a controller and guarantor of the survival of the population due to the loss of population access to independent survival